Pengembangan Modul Praktikum Kimia Berbasis Green Chemistry Pada Materi Kesetimbangan Kimia Untuk Meningkatkan Minat Belajar Siswa Kelas XI - Disa, Raka Rangga; Muntari, Muntari; Hadisaputra, Saprizal (Chemistry Education Practice, 2024)
This study aims to determine the feasibility, practicality, and effectiveness of the green chemistry-based chemistry practicum module on chemical equilibrium material to increase student interest in learning. The research uses the R&D (Research and Development) 4-D model modified into three steps (3-D), namely Define, Design, Develop. This design was modified into three steps due to the limitations of the researcher to carry out the fourth stage of Disseminate. The results of the validity assessment by a validator consisting of two chemistry education lecturers based on the Aiken'V index of 0.77 (valid or feasible). The practical assessment of the chemistry practicum module by the class XI chemistry teacher was tested practically with a percentage of 92.67% (very practical) and received a good response from students in class XI MIPA 2 with an average percentage of 88.15% (very practical). The results of the effectiveness of the practicum module are taken from student interest in learning data, based on the learning interest category index, the average value is 4.22 (effective). The results of the study indicate that the green chemistry-based chemistry practicum module on the chemical equilibrium material developed is feasible, practical and effective to increase student interest in learning